Modulation of Allergic Reactivity in Humans Is Dependent on Schistosoma mansoni Parasite Burden, Low Levels of IL-33 or TNF-α and High Levels of IL-10 in Serum - Resende, Samira D.; Magalhães, Fernanda C.; Rodrigues-Oliveira, Jailza L.; Castro, Vanessa N.; Souza, Carolina S. A.; Oliveira, Edward J.; Carneiro, Mariângela; Geiger, Stefan M.; Negrão-Corrêa, Deborah A. (Frontiers in Immunology, 2019)
Helminth infections and allergies are characterized by a predominant type-2 immune response. In schistosomiasis, the Th-2 response is usually accompanied by induction of immunoregulatory mechanisms that contribute to worm survival and less severe schistosomiasis. Although helminth-induced immunomodulatory mechanisms seem to affect atopy, epidemiological studies on the relationship between helminths and allergy have been inconsistent, and data suggest that the modulatory effects may be influenced by helminth species, chronicity of infection, and parasite burden. Here we performed a cross-sectional study to investigate the effects of Schistosoma mansoni parasite burden and immune response on allergic reactivity of individuals living in a schistosomiasis endemic area in Brazil. Fecal samples from volunteers aging six to 75 years old were collected for extensive parasitological examinations by spontaneous sedimentation, Kato-Katz, Helmintex and Saline Gradient tests and molecular detection of S. mansoni by qPCR. Additionally, the concentrations of cytokines and chemokines, total IgE and IgE-reactivity to common house dust allergens were quantified from serum samples. IgE reactivity to dust allergens was detected in 47 individuals (23.8%), and 140 individuals (54.4%) were diagnosed with S. mansoni infection. Most of the infected population (108 individuals) presented very low parasite burden (≤ 12 eggs/g of feces). The frequency and intensity (p  0.03) of allergic reactivity were lower in S. mansoni-infected compared with non-infected individuals. Multivariable logistic regression models adjusted by age revealed that allergic reactivity was positively associated with low IL-10 response (OR, 4.55, 95% CI, 0.56–7.36) and high concentration of the inflammatory mediators IL-33 (OR, 2.70, 95% CI, 1.02-7.15) or TNF-α (OR, 6.88, 95% CI, 0.32-143.39) in serum, and inversely associated with S. mansoni infection (OR, 0.38, 95% CI, 0.16-0.87). Most importantly, the logistic regression demonstrated that the modulatory effects of Schistosoma infection depend on parasite burden, with individuals infected with ≤ 12 eggs/g of feces showing allergic IgE-reactivity similar to non-infected individuals Altogether, our data show that immunomodulation of allergic reactivity depends on S. mansoni burden, low type-2 inflammatory response, and high level of IL-10.